Effects of Axial Functional Groups on Heterogeneous Molecular Catalysts for Electrocatalytic CO2 Reduction. Issue 11 (30th September 2021) - Sun, Libo; Reddu, Vikas; Su, Tan; Chen, Xinqi; Wu, Tian; Dai, Wei; Fisher, Adrian C.; Wang, Xin
Abstract : Recent years have witnessed the development of heterogeneous molecular catalysts toward electrocatalytic CO2 reduction. One effective strategy for such heterogenization is to decorate molecular catalysts directly through axial coordination to functionalized carbon substrates and it will be interesting to elucidate the influence of such functional groups on the activity. Herein, it is demonstrated that among several kinds of N‐, O‐, and S‐derived functional groups‐decorated carbon nanotubes, pyridine‐based ones may play the role of a suitable linker and assist in achieving higher activity toward CO2 reduction by a molecular catalyst. Density functional theory (DFT) calculation is also carried out to support the experimental results. This observation provides more insights into how a substrate can influence the intrinsic catalytic behavior of molecular catalysts via functional groups without venturing into the complexities involved with the synthesis of novel ligands. Abstract : Through axial coordination of molecular catalysts with pyridine‐functionalized multiwalled carbon nanotubes, both the activity and selectivity of the molecular catalyst toward electrocatalytic CO2 reduction are improved. The calculation shows that the improvement is correlated with the increase in electron density and reorganization of dz 2 orbital for cobalt atoms by the axial pyridine functionalization.